(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article analyzes the methodology for planning and conducting problem-activity lessons in physics and the structure of the experimental system in school physics. The seven stages of a problem-activity lesson - from creating a problem situation through consolidation of new knowledge and reflection - are presented in detail. Four types of school physics experiments are classified: demonstration experiments, frontal laboratory work, physics practical sessions, and extracurricular experiments and observations - with identification of their didactic functions.